Analisis Perencanaan dan Pengendalian Persediaan Obat Antibiotik di RSUD Cicalengka Tahun 2014 - Kencana, Gita Gilang (UI Scholars Hub, 2016)
Poor planning and controlling of drug in RSUD Cicalengka has resulted excess inventory and potential Hospital losses. This operational research was using ABC Critical Index Analysis Method, Safety Stock, Economic Order Quantity (EOQ) and Reorder Point (ROP). Stock evaluation using Inventory Turnover Ratio (ITOR) was also conducted. The result of ABC Critical Index Analysis showed that were seven antibiotics need to be prioritized. The estimation of antibiotic drug in group A for year 2015 was done using Single Exponential Smoothing Method. Safety stock for Cefadroxil Kaps 500 mg (5x10) as much as 344, EOQ as much as 1476 and ROP as much as 977. The result of ITOR figure was 8.1 and after analysis it was 19.6. The study suggested RSUD Cicalengka to implement planning and controlling of drug in the hospital.